Analysing the Demography and Migration Related Challenges within the Internal Periphery of South-Heves - Tunde Bogardi (DETUROPE)
The purpose of my study is to perform an analysis with the application of regional statistical data, in order to understand the changes within the number of the population at South-Heves in the past period, and to the reveal its special characteristics compared to regional, national trends. The examined area is a classic internal periphery, a region “hit severely by social, economic and environmental crisis” (according to the draft proposal of Heves county’s regional development concept (2014-2020)). Considering such regions, besides the examination of the intention to migrate, it is also important to see who will remain in the region. Experiences show that in case of regions with a more disadvantageous situation than average, generally classes of lower social statuses will become dominant, while as it is described by Győri-Nagy (2003), “the escape of competent classes of the population” can be observed. It results in a contra-selected local society which is unable to retain the young and ambitious. The future of the affected regions, settlements is largely determined by the perspectives perceived by young people who live there, and who shall start their families and careers there in the near future. I have conducted an empirical research amongst high-school students living and studying at South-Heves, focusing on issues such as whether the high-school age-group of this classic periphery is considering migration; if so, then what are the reasons, destinations, and as an important question from the aspect of the national strategy as well, how could these young people who are longing to go elsewhere manage their lives here, and how could we make them stay in their homeland (in a narrow sense). By investigating the intention to migrate, we also receive indirect answers for questions such as how could significant regional differences be reduced, and how could we close the gap in case of the most disadvantageous regions.